Reading glossed passages in English to improve comprehension : an eye tracking study - Izzammuddin Isnin; Nurjanah Mohd Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2021)
Glosses or short explanations of vocabulary items are commonly found in language learning materials. Research that use offline learning measures to examine effects of glosses on learning found that they are useful in facilitating vocabulary acquisition and overall text comprehension. This paper reports a small-scale study that combined an offline measure of learning with online measures of reading behaviour in an attempt to provide a more comprehensive picture of reading and learning with glossed passages. The eye tracking methodology was used to provide insights into the cognitive processing of reading. A group of 15 university undergraduates read four glossed and non-glossed passages in English and answered comprehension questions afterwards. The findings revealed that glossed and non-glossed passages were read differently with readers attempting to integrate glosses and text information in the former. Vocabulary knowledge was found to predict comprehension performance and to some extent, the processing of glosses. The findings also suggest that moderate amount of attention could be more useful for comprehension as too much attention appeared to indicate comprehension difficulties. Suggestions to promote more strategic and useful processing of glossed passages are discussed.